Improvement of energy absorption on magnesium alloy mixed carbon-nanotube and lead reinforcement materials in terms of high velocity impact - Abdullah, Mohamad Faizal; Andullah, Shahrum; Omar, Mohd Zaidi; Sajuri, Zainudin; Mohd Sohaimi, Risby (International Journal of Integrated Engineering, 2018)
This paper presents the fracture behaviour of magnesium alloy (AZ31B) with the reinforcement of carbon-nanotube (CNT) and lead subjected ballistic impact. Magnesium alloys are material that can absorb impact energy, however the absorption energy can be increased with the alloy reinforcement with nano-partial. This paper leads to two parts which are experiment and simulation of gas gun. The projectile used was a cone-nose type with diameter of 11 mm made by steel series 1006. The simulation used Cowper-Symonds model to see material behaviour with 25 mm thickness. The correlation of the experiment and simulations was evaluated to see the accuracy of simulations made. It was shown that the value of R2 was 0.9588 where simulation can be used to predict the ballistic impact on 600 m/s velocity. From the simulation results, it was found that the depth of penetration for Magnesium alloy AZ31B reinforced with CNT and Pb showed good agreement findings. The depth of penetrations onto the simulation were obtained between 15 to 25 mm. The added reinforcement materials provide a reduction in the depth of penetration of 40% compared to the original Magnesium alloy AZ31B. Thus, this type of magnesium alloy reinforced with CNT and Pb is suitable for ballistic resistant panel with weight saving determination on armoured vehicle.Â